Influencing Factors of Profitability in the Textile Sector: The Role of Firm Size - Hina Waheed; Sayyid Salman Rizavi; Shaista Jabeen; Muhammad Farhan (`, 2025)
The profitability of Pakistan’s textile industry is examined in this study, with a focus on firms that are listed on the Pakistan Stock Exchange. The aim of this study is to investigate how profitability metrics like net profit margin (NPM), return on assets (ROA), and return on equity (ROE) are impacted by factors that include debt, cash conversion cycle, operational cycle, firm size, and current ratio. For the time span of 2018–2022, panel data from 76 textile enterprises is analyzed using fixed and random effect models. Results reveal that leverage has a substantial effect on ROA and ROE and that fewer cash conversion cycles are preferred for ROA and NPM and longer cycles are superior for ROE. ROE is negatively affected by the operational cycle, but not ROA or NPM. The relationship between the cash conversion cycle and profitability is mediated by the size of the firm. The study presents valuable data that helps academics, industry experts, and officials make strategic decisions on debt control and operations efficiency in the textile sector. Keywords: Profitability, Leverage, Size, Cash Conversion Cycle